2001
DOI: 10.1067/mhn.2001.116788
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Reconstruction of the Head and Neck: Analysis of 241 Cases

Abstract: Risk to patients and transferred tissue is low in free flap head and neck reconstruction. Age, smoking history, and weight loss should be considered during patient selection. Fluid balance should be considered during and after surgery. Division of labor for patient care should be carefully delineated among surgeons in a teaching setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
313
7
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(355 citation statements)
references
References 17 publications
26
313
7
9
Order By: Relevance
“…Moreover, this flap offers excellent bicortical bone stock for dental implant placement and a versatile cutaneous unit for soft-tissue reconstruction. 9,[15][16][17][19][20][21][22][23][24] Once dehiscence occurs, the vital periosteum accelerates the re-epithelialisation and healing. 16 The muscle-sparing technique diminishes the donor-site dead space and subsequent haematoma, reduces the risk of the pedicle damage, promotes the skin-island pliability, and preserves the donor limb strength.…”
Section: A Rational Approach For Treating Ameloblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this flap offers excellent bicortical bone stock for dental implant placement and a versatile cutaneous unit for soft-tissue reconstruction. 9,[15][16][17][19][20][21][22][23][24] Once dehiscence occurs, the vital periosteum accelerates the re-epithelialisation and healing. 16 The muscle-sparing technique diminishes the donor-site dead space and subsequent haematoma, reduces the risk of the pedicle damage, promotes the skin-island pliability, and preserves the donor limb strength.…”
Section: A Rational Approach For Treating Ameloblastomamentioning
confidence: 99%
“…19,22,28 The early recognition and timely management of flap complications is necessary because of a narrow window of opportunity to salvage potential flap failure. 14 A large series by Bui et al 14 revealed many factors involving venous thrombosis following MHNR, including the use of a vein graft, kinking or compressing of the veins with tight skin closure, neck motion, and end-to-end venous anastomoses.…”
Section: Compromised Vascularity and Free Flap Failurementioning
confidence: 99%
“…Wielu autorów zajmujących się tematyką powikłań pooperacyjnych uważa zapalenie płuc za jedną z głównych przyczyn zgonów pooperacyjnych [7,76,126,190].…”
Section: Powikłania Ze Strony Układu Oddechowegounclassified
“…Obszerne piśmiennictwo nie wskazuje jednak na taki mechanizm. Chociaż oddzielenie otyłości od innych czynników ryzyka występujących u osób otyłych jest trudne, prace wykorzystujące analizy wieloczynnikowe również nie wykazały wzrostu powikłań płucnych u chorych z otyłością [10,76,126,131,196,223]. W naszym materiale także nie stwierdziliśmy wyższego wystę-powania powikłań płucnych o osób otyłych.…”
Section: Powikłania Ze Strony Układu Oddechowegounclassified
“…Free flap transfers have proved highly effective in the reconstruction of complex defects in the head and neck region [1][2][3][4][5][6][7]. Despite excellent results, postoperative thrombosis does occur and, although infrequent, causes total loss of the flap.…”
Section: Introductionmentioning
confidence: 99%